Boronic acids in saccharide recognition - James, Tony D. (RSC Pub., 2006)
The desire to quantify the presence of analytes within diverse physiological, environmental and industrial systems has led to the development of many novel detection methods. In this arena, saccharide analysis has exploited the pair-wise interaction between boronic acids and saccharides. Boronic Acids in Saccharide Recognition provides a comprehensive review and critical analysis of the current developments in this field. It also assesses the potential of this innovative approach, outlining future lines of research and possible applications. Topics include: the molecular recognition of saccharides, the complexation of boronic acids with saccharides, fluorescent sensors and the modular construct of fluorescent sensors, further sensory systems for saccharide recognition and an extensive bibliography. This high level book is ideal for researchers both academic and industrial who require a comprehensive overview of the subject.
Keywords: Saccharides.; elektronické knihy; electronic books